DETERMINATION OF GREYWATER REUSE POTENTIAL IN DAMATURU YOBE STATE, NIGERIA - Shettima Lawan, Muhammad; Bukar, Mohammed; Gide, Suleiman (FUDMA JOURNAL OF SCIENCES, 2022)
Greywater reuse is an untapped available water resource for many rural areas in developing countries. Meanwhile, it is one of the alternative ways to overcome water scarcity in many parts of the world. This study was carried out to investigate the potential of Greywater reuse as a means to overcome the problem of water scarcity and environmental pollution among restaurants and hotel owners within Damaturu metropolis in Yobe State of Nigeria. A field survey was conducted from 25 restaurants/hotels operating within Damaturu and Greywater samples were collected for reclamation using rice husk as a filter. The results of the survey indicated that the majority of the respondents expressed the problem of water scarcity and about 99% mentioned that they rely on buying multiple water trucks for their daily needs. The survey further revealed that 76% of the respondents fully agreed with greywater reuse, while 12% disagreed, and the rest of the respondents (10%) remain undecided. Physical parameters including; Total Dissolved Solids (TDS), Total Suspended Solids (TSS), pH, and Turbidity as well as general coliforms were determined before and after treatment with normal and chemically modified rice husk. However, an insignificant treatment efficiency was observed in the laboratory scale experiment with the normal rice husk which indicates the requirement for further modification. However, modification of the rice husk filter with an acidic reagent was confirmed to increase pH and electrical conductivity of the filter media, and determination of the retention time is always important in developing a greywater system
Keywords: Greywater, Water scarcity, TDS, TSS, Turbidity